Development and Validation of Multiscale Coupled Thermal-Hydraulic Code Combining RELAP5 and Fluent Code - Sun, Lin; Peng, Minjun; Xia, Genglei; Wang, Xuesong; Wu, Mingyu (Frontiers in Energy Research, 2021)
In nuclear reactor system research, multiscale coupled thermal-hydraulic (T-H) system code and CFD code is one of the most concerned research areas, and it could help improve simulation fidelity and optimize nuclear reactor design. Additionally, a new idea called function fitting method (FFM) for coupling parameter distribution has been first proposed for exchanging data on the coupling interface, which uses math equation to present the velocity distribution characteristics at the coupling interface. This method could improve the simulation error and numerical instability. To verify and validate the abovementioned FFM, the comparison between the velocity function shape by FFM and real velocity distribution have been done. Besides, the Edwards pipe blowdown test results have been used to verify the coupled code. The results showed good agreement with experiment results, also a better simulation accuracy compared to previous work. The current work will bring about the ability to explore multiscale coupled thermal-hydraulic operation characteristics which give more precise local parameters distribution.